Project-based learning to create effective biology teaching - Beluan, Caesilia Somi; Nebore, Idola Dian Yoku; Jeni, Jeni (Inornatus: Biology Education Journal, 2018)
This research aims to create effective biology teaching to improve student learning outcomes and activeness using project-based learning (PjBL). Classroom action research (CAR) was used to create effective learning. A total of 24 students became the subject of this CAR. They are in class XI IPA. Students were observed for three meetings using the observation sheet to measure attitudes, skills, and activity. We were measuring students' cognitive learning outcomes using tests. The CAR results showed that 79.16% of students achieved a minimum standard of 70. A total of 66.67% achieved skills from good to very good. Student activity and teacher activity has increased. This CAR concludes that PjBL effectively improves biology learning and improves students' learning outcomes. Some students have not reached the good category, so further research in the use of PjBL can be improved.